Colorectal endometriosis: Diagnosis, surgical strategies and post-operative complications - Alborzi, Saeed; Roman, Horace; Askary, Elham; Poordast, Tahereh; Shahraki, Mahboobeh Hamedi; Alborzi, Soroush; Hesam Abadi, Alimohammad Keshtvarz; Najar Kolaii, Elnaz Hosseini (Frontiers in Surgery, 2022)
Objective: The present work aimed to investigate the feasibility, complications, recurrence rate, and infertility outcomes of the radical and conservative surgical methods for colorectal endometriosis in short- and long-term follow-ups. Methods: In this prospective study, the patients with confirmed diagnosis of colorectal DIE were included from March 2015 to March 2021, who were referred to an Endometriosis Surgery Center affiliated with Shiraz University of Medical Sciences (SUMS). Information on demographics, surgical approaches, intra-operative, and post-operative findings as well as complications were collected and compared. Six- and 12-month interviews were conducted to evaluate the functional outcomes of all the procedures. Results: Out of 3111 patients who underwent endometriosis surgery, 837 (28.19%) with the average age of 34.2 ± 5.9 years and average ASRM score of 102.1±36.8 had rectosigmoid endometriosis. Laparoscopic rectal shaving was performed in 263(30.0%) patients while 326 (37.2%) underwent segmental bowel resection, and 248 (28.30%) were treated with disc excision. Prophylactic ileostomy was performed in six (0.68%) patients and peritonitis was reported in four (0.45%). Five (0.58%) subjects developed rectovaginal fistula and one (0.11%) was diagnosed with bladder atonia. The recurrence rate was 3.8%, 1.2%, and 0.3% in rectal shaving, disc, and segmental bowel resection techniques, respectively. Dysmenorrhea, dyspareunia, and dyschezia were improved after surgery by 7.3, 9.4, and 12.5 times, respectively. We observed 25.2% of total pregnancy following the operation, the majority of which occurred in the first year after the surgery. Conclusion: There were very few short-term or long-term complications in the three different techniques when the choice was correct.